Preparation method and application of composite proton exchange membrane

Doping precious metal ions in high-pressure PEM water electrolytic reactors through precious metal impregnation reduction method solves the problems of gas permeation and structural damage, and realizes low hydrogen permeation and high-performance membrane electrodes, improving safety and catalyst utilization.

CN119571391AActive Publication Date: 2025-03-07DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411772994.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

In high-pressure PEM water electrolytic reactors, the water absorption characteristics of the membrane lead to gas permeability problems, affecting safety and efficiency, and traditional doping methods lead to structural damage and high precious metal loads.

Method used

Through the precious metal impregnation reduction method, precious metal ions are doped into the anode side of the film, and the uniform distribution of precious metal particles is achieved by using longitudinal impregnation and in-situ reduction techniques to reduce the load of precious metals.

Benefits of technology

It effectively reduces the hydrogen permeability of the membrane electrode, improves product purity and safety, and the uniform distribution of precious metals improves the utilization rate of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571391A_ABST
    Figure CN119571391A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of proton exchange membrane electrolyzed water, in particular to a preparation method and application of a composite proton exchange membrane. The migration of noble metal ions in the membrane is realized by utilizing pH gradient and ion gradient, the noble metal ions are doped into one side of an anode of the membrane, uniform distribution of noble metal particles in the membrane is realized by utilizing a longitudinal dipping mode, and then the time of reduction through in-situ sodium borohydride is controlled, and the doping amount of a hydrogen elimination catalyst is controlled, so that the hydrogen elimination efficiency is improved. And preparing the ultralow noble metal loading capacity composite membrane. The composite proton exchange membrane is prepared through precious metal impregnation reduction, the performance is guaranteed, meanwhile, the hydrogen permeation amount of a membrane electrode is reduced, the hydrogen content in anode side oxygen is reduced, the product purity is improved, and meanwhile, the safety is improved. The uniform distribution of the noble metal fully improves the utilization rate of the catalyst, so that the catalyst coating film can obtain an excellent hydrogen elimination effect when a small amount of noble metal is impregnated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of proton exchange membrane water electrolysis, and in particular to a composite proton exchange membrane preparation method and application thereof. Background Art

[0002] Hydrogen is considered to play an important role in decarbonization and sustainable energy systems, as an alternative energy carrier or fuel produced in future renewable energy sources. The production and use of hydrogen through electrochemical cells is the most promising way to achieve its widespread commercialization. Water electrolysis is a reaction that electrochemically decomposes water into hydrogen and oxygen. Proton exchange membrane (PEM) water electrolysis has been widely studied due to its advantages such as using pure water as a reactant, compact structure, high operating current density, high gas production, high purity of hydrogen produced, fast response speed and high operating pressure allowed. It has also been applied to fuel cell hydrogen supply, industrial raw materials, medical treatment and other fields through coupling with green electricity.

[0003] Compared with the traditional PEM water electrolysis at normal pressure, the PEM water electrolyzer working in high-pressure mode can provide hydrogen to the end user at high pressure, requiring minimal energy to further compress and store hydrogen, reducing costs while improving the maximum voltage efficiency. Therefore, high-pressure PEM water electrolysis is currently a research hotspot. However, due to the water absorption characteristics of the membrane, there is still a gas permeation problem during the operation of the high-pressure PEM water electrolysis stack. In the low current density region, gas permeation is closely related to safety and efficiency, while in the high current density region, permeation affects the attenuation of the membrane. Therefore, the preparation of low hydrogen permeation and high-performance membrane electrodes is crucial for the safe and efficient operation of water electrolysis stacks.

[0004] In order to solve the above problems, patent CN104726891A discloses a proton exchange membrane water electrolyzer with internal hydrogen removal function and its manufacturing method. By modifying the hydrogen removal catalyst on the surface of the current collector and the bipolar plate behind the membrane electrode, hydrogen and oxygen can generate water through electrochemical reaction on the catalyst surface, thereby realizing the hydrogen removal inside the water electrolyzer stack. However, this method has high requirements on the catalyst loading, and it may be difficult to eliminate hydrogen outside the membrane electrode under high pressure. Patent CN116926618A discloses a method for preparing a catalyst-coated proton membrane with a composite catalytic layer structure, which reduces the hydrogen permeation during the water electrolysis process by adding a functional layer of hydrogen removal precious metal catalyst between the anode catalyst layer and the proton exchange membrane. However, adding a functional layer will increase the thickness of the membrane electrode, and it is difficult to achieve a uniform distribution of low-load precious metals. Summary of the invention

[0005] In order to solve the defects of the prior art, the present invention provides a composite proton exchange membrane preparation method and its application. The present invention dopes the noble metal ions into the anode side of the membrane through noble metal impregnation reduction, reduces the hydrogen permeation of the membrane electrode while ensuring the performance, reduces the hydrogen content in the oxygen on the anode side, improves the product purity, and improves safety. The composite proton exchange membrane has good proton conductivity and does not require phosphoric acid during the preparation process.

[0006] In order to achieve the above object, the technical solution of the present invention is as follows:

[0007] In one aspect, the present invention provides a method for preparing a composite proton exchange membrane, the method comprising the following steps:

[0008] (1) dissolving a compound containing a noble metal ion in water, stirring thoroughly to dissolve, and adjusting the pH to 7 to 13 to obtain a solution S1;

[0009] (2) dissolving K2SO4 in water, stirring thoroughly to dissolve, and adjusting the pH to 1 to 3 to obtain solution S2;

[0010] (3) washing the proton exchange membrane M1 with acid and then with water to obtain an activated membrane M2;

[0011] (4) adding solution S1 and solution S2 to both sides of the activated membrane M2 and immersing the membrane M3 in a longitudinal direction; the longitudinal direction means that the membrane is parallel to the bottom of the immersion container, and solution S1 and solution S2 are located on the upper and lower sides of the membrane, respectively;

[0012] (5) dissolving NaBH4 in water, stirring thoroughly to dissolve, and adjusting the pH to 7 to 13 to obtain solution S3;

[0013] (6) adding solution S3 to the upper side of membrane M3 for reduction treatment to obtain membrane M4;

[0014] (7) The membrane M4 is acid-washed and water-washed to obtain the composite proton exchange membrane.

[0015] In the preparation method of the present invention, the raw materials of the composite proton exchange membrane include a catalyst and a proton exchange membrane, wherein: the catalyst is a catalyst that can catalyze hydrogen oxidation reaction to generate water, including precious metal catalysts such as Pt, Pd and their composites; the proton exchange membrane is a proton exchange membrane that can undergo ion exchange with precious metals, including a perfluorosulfonic acid membrane and a perfluorosulfonic acid-based composite membrane.

[0016] Based on the above technical solution, preferably, in the step (1), the molar concentration of the compound containing noble metal ions in the solution S1 is 0.4-4 mM; KOH is used to adjust the pH;

[0017] In the step (2), the molar concentration of K2SO4 in the solution S2 is 0.01 to 0.1 M; H2SO4 is used to adjust the pH;

[0018] In the step (3), the acid used for pickling is 0.5M H2SO4;

[0019] In the step (5), the molar concentration of NaBH4 in the solution S3 is 0.2 to 1 M; KOH is used to adjust the pH;

[0020] In the step (7), the acid used for pickling is HClO4 or H2SO4, and its molar concentration is 1 to 5M.

[0021] Based on the above technical solution, preferably, in step (1), the compound containing precious metal ions is one or more of Pt(NH3)4(NO3)2, Pt(NH3)4Cl2, Pd(NH3)4(NO3)2, and Pd(NH3)4Cl2;

[0022] Based on the above technical solution, preferably,

[0023] When the compound containing precious metal ions is a Pt compound, the pH in steps (1) and (5) is independently 10 to 13; when the compound containing precious metal ions is a Pd compound, the pH in steps (1) and (5) is independently 7 to 11; when the compound containing precious metal ions is a combination of a Pt compound and a Pd compound, the pH in steps (1) and (5) is independently 10 to 11.

[0024] Based on the above technical solution, preferably, in the step (3), the temperature of pickling and water washing is 80°C, the time of pickling is 30 to 60 minutes, and the time of water washing is 30 to 60 minutes;

[0025] In the step (4), the immersion temperature is 30 to 40° C. and the immersion time is 1 to 24 hours;

[0026] In the step (6), the reduction temperature is 30 to 40° C. and the reduction time is 30 to 90 min;

[0027] In the step (7), the acid pickling temperature is 20°C, the acid pickling time is 12 to 48 hours, and the water washing temperature is 80°C, and the water washing time is 30 to 60 minutes.

[0028] Another aspect of the present invention provides a composite proton exchange membrane prepared by the above method.

[0029] The present invention also provides a membrane electrode, comprising a composite proton exchange membrane, and an anode catalyst layer located on one side impregnated with a precious metal and a cathode catalyst layer located on the opposite side, wherein the composite proton exchange membrane is the composite proton exchange membrane mentioned above.

[0030] Based on the above technical solution, preferably, the anode catalyst layer includes an anode catalyst and an ionomer 1, the anode catalyst includes one or more of an Ir-based catalyst, a Ru-based catalyst and an IrRu composite catalyst, and the ionomer 1 is a perfluorosulfonic acid resin;

[0031] The cathode catalyst layer includes a cathode catalyst and an ionomer 2. The cathode catalyst includes one or more of a Pt-based catalyst and a Pd-based catalyst. The ionomer 2 is a perfluorosulfonic acid resin.

[0032] Based on the above technical solution, preferably, the anode catalyst includes Ir, IrOx, Ru, RuOx, IrRuOx, IrY alloy, RuY alloy, IrRuY alloy and corresponding catalysts with carriers, wherein Y is selected from one or more of Pt, Pd, Au, Ag, Fe, Co, Ni, Cu and Mn;

[0033] The carrier includes one or more of carbon, titanium dioxide, and tungsten oxide.

[0034] Based on the above technical scheme, preferably, the Pt-based catalyst includes one or more of Pt / C, Pt, and PtM alloys, and the Pd-based catalyst includes one or more of Pd / C, Pd, and PdM alloys, wherein M is selected from one or more of Ir, Ru, Au, Co, Fe, Cu, and Ni.

[0035] Based on the above technical scheme, preferably, the preparation method of the anode catalyst layer and the cathode catalyst layer is: the anode catalyst and the cathode catalyst are independently mixed with a perfluorosulfonic acid resin and a solvent to obtain a corresponding catalyst slurry, and then the anode catalyst layer and the cathode catalyst layer are prepared on the surface of the proton exchange membrane by spraying, coating or transfer method; the solvent includes one or more of water, methanol, ethanol, ethylene glycol, n-propanol, and isopropanol.

[0036] The present invention also provides an application of the membrane catalyzing electrode in a water electrolysis cell.

[0037] The beneficial effects of the present invention are:

[0038] (1) The present invention prepares a composite proton exchange membrane by noble metal impregnation reduction, utilizes pH gradient and ion gradient to realize the migration of noble metal ions in the membrane, dopes the noble metal ions into the anode side of the membrane, and realizes the uniform distribution of noble metal particles in the membrane by longitudinal impregnation, and then controls the time of in-situ sodium borohydride reduction and the doping amount of hydrogen removal catalyst to prepare an ultra-low noble metal loading composite membrane. Using the above method, the doping of noble metals has little damage to the structure of the membrane, solving the problem of structural damage caused by traditional doping.

[0039] (2) In the preparation method of the present invention, the problem that the precious metals are mostly deposited in the lower half due to gravity to form a gradient in the existing process, which makes it impossible to reduce the loading and uniformly dehydrogenate, is solved by longitudinal impregnation. The lower layer of liquid is removed during the reduction process to solve the problem of point-like reduction due to gas diffusion, thereby obtaining a composite film uniformly impregnated with precious metals and realizing a uniform dehydrogenation function inside the electrode. By adjusting the pH, ultra-low loading impregnation of Pd, which is difficult to impregnate, is achieved, and while ensuring the electrode performance, the same dehydrogenation effect as impregnated Pt is achieved.

[0040] (3) In the preparation method of the present invention, the noble metal catalyzes the oxidation of hydrogen permeated in the membrane to generate water, thereby reducing the hydrogen permeation of the membrane electrode while ensuring performance, reducing the hydrogen content in the oxygen on the anode side, and improving product purity while improving safety. The uniform distribution of the noble metal fully improves the utilization rate of the catalyst, so that the catalyst-coated membrane can achieve excellent hydrogen removal effect when a small amount of noble metal is impregnated. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a schematic diagram of the structure of the clamp for fixing the film used in the present invention;

[0042] Figure 2 A schematic diagram of the fixture structure for fixing the film in Comparative Example 2;

[0043] Figure 3 Schematic diagram of composite membranes prepared in Example 1, Comparative Example 2 and Comparative Example 4, a is Example 1, b is Comparative Example 2, and c is Comparative Example 4;

[0044] Figure 4 This is a curve diagram showing the change of hydrogen content in oxygen on the anode side of a water electrolysis cell assembled with the composite membranes prepared in Comparative Example 1, Example 1 and Example 2 as a function of current density. DETAILED DESCRIPTION

[0045] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.

[0046] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained through commercial channels or prepared according to conventional methods well known to those skilled in the art.

[0047] Example 1

[0048] (1) Dissolve Pt(NH3)4(NO3)2 in water, stir thoroughly to obtain a 0.4 mM Pt(NH3)4(NO3)2 solution, add KOH and adjust the pH to 13;

[0049] (2) Dissolve K2SO4 in water, stir thoroughly to obtain a 0.013M K2SO4 solution, add H2SO4, and adjust the pH to 1;

[0050] (3) treating the Nafion 212 membrane in 0.5 M H2SO4 at 80°C for 30 min, then treating it in ultrapure water at 80°C for 30 min, and washing it until the pH is 7 to obtain a treated membrane;

[0051] (4) According to Figure 1 The membrane is fixed in a manner, with the platinum-containing solution obtained in step (1) being located in the upper layer, and the potassium sulfate solution obtained in step (2) being located in the lower layer, and the membrane treated in step (3) being immersed in the solution longitudinally at 30° C. for 1 hour;

[0052] (5) Dissolve NaBH4 in water, stir thoroughly to obtain a 0.2M NaBH4 solution, add KOH and adjust the pH to 11;

[0053] (6) Pour out the solutions on both sides, replace the upper solution with 0.2 M NaBH4 (pH = 11, KOH) obtained in step (5), and reduce at 30°C for 60 min;

[0054] (7) The membrane obtained in step (6) was taken out, washed three times with ultrapure water, treated with 5M HClO4 at room temperature for 48 h, treated with ultrapure water at 80°C for 30 min, and then washed with ultrapure water to obtain a composite membrane.

[0055] The Ir loading was 1 mg cm-1 sprayed on the Pt-impregnated side of the composite membrane. -2 The catalyst layer on the other side was sprayed with a Pt loading of 0.4 mg cm -2 The catalyst layer is formed to obtain a membrane electrode.

[0056] Example 2

[0057] (1) Dissolve Pd(NH3)4(NO3)2 in water and stir thoroughly to obtain a 0.4 mM Pd(NH3)4(NO3)2 solution (pH = 7);

[0058] (2) Dissolve K2SO4 in water, stir thoroughly to obtain a 0.013M K2SO4 solution, add H2SO4, and adjust the pH to 1;

[0059] (3) treating the Nafion 212 membrane in 0.5 M H2SO4 at 80°C for 30 min, then treating it in ultrapure water at 80°C for 30 min, and washing it until the pH is 7 to obtain a treated membrane;

[0060] (4) According to Figure 1The membrane is fixed in a manner, with the palladium-containing solution obtained in step (1) being located on the upper layer, and the potassium sulfate solution obtained in step (2) being located on the lower layer, and the membrane treated in step (3) being immersed in the solution longitudinally at 30° C. for 1 hour;

[0061] (5) dissolving NaBH4 in water and stirring thoroughly to obtain a 0.2 M NaBH4 solution (pH = 7);

[0062] (6) Pour out the solutions on both sides, replace the upper solution with 0.2 M NaBH4 obtained in step (6), and reduce at 30°C for 60 min;

[0063] (7) The membrane obtained in step (6) was taken out, washed three times with ultrapure water, treated with 1M H2SO4 at room temperature for 48 h, treated with ultrapure water at 80°C for 30 min, and then washed with ultrapure water to obtain a composite membrane.

[0064] The Pd-impregnated side of the composite membrane was sprayed with Ir at a loading of 1 mg cm -2 The catalyst layer on the other side was sprayed with a Pt loading of 0.4 mg cm -2 The catalyst layer is formed to obtain a membrane electrode.

[0065] Example 3

[0066] (1) Dissolve Pt(NH3)4Cl2 in water, stir thoroughly to obtain a 0.4 mM Pt(NH3)4Cl2 solution, add KOH and adjust the pH to 13;

[0067] (2) Dissolve K2SO4 in water, stir thoroughly to obtain a 0.013M K2SO4 solution, add H2SO4, and adjust the pH to 1;

[0068] (3) treating the Nafion 212 membrane in 0.5 M H2SO4 at 80°C for 30 min, then treating it in ultrapure water at 80°C for 30 min, and washing it until the pH is 7 to obtain a treated membrane;

[0069] (4) According to Figure 1 The membrane is fixed in a manner, the platinum-containing solution obtained in step (2) is located in the upper layer, the potassium sulfate solution obtained in step (2) is located in the lower layer, and the membrane treated in step (3) is immersed in the solution longitudinally at 30° C. for 1 hour;

[0070] (5) Dissolve NaBH4 in water, stir thoroughly to obtain a 0.2M NaBH4 solution, add KOH and adjust the pH to 11;

[0071] (6) Pour out the solutions on both sides, replace the upper solution with 0.2 M NaBH4 (pH = 11, KOH) obtained in step (5), and reduce at 30°C for 60 min;

[0072] (7) The membrane obtained in step (6) was taken out, washed three times with ultrapure water, treated with 5M HClO4 at room temperature for 48 h, treated with ultrapure water at 80°C for 30 min, and then washed with ultrapure water to obtain a composite membrane.

[0073] The Ir loading was 1 mg cm-1 by blade coating on the Pt-impregnated side of the composite membrane. -2 The catalyst layer on the other side was coated with Pt with a loading of 0.4 mg cm -2 The catalyst layer is formed to obtain a membrane electrode.

[0074] Example 4

[0075] (1) Dissolve Pt(NH3)4(NO3)2 in water, stir thoroughly to obtain a 0.4 mM Pt(NH3)4(NO3)2 solution, add KOH and adjust the pH to 13;

[0076] (2) Dissolve K2SO4 in water, stir thoroughly to obtain a 0.013M K2SO4 solution, add H2SO4, and adjust the pH to 1;

[0077] (3) treating the Nafion 115 membrane in 0.5 M H2SO4 at 80°C for 30 min, then treating it in ultrapure water at 80°C for 30 min, and washing it until the pH is 7 to obtain a treated membrane;

[0078] (4) According to Figure 1 The membrane is fixed in a manner, with the platinum-containing solution obtained in step (1) being located in the upper layer, and the potassium sulfate solution obtained in step (2) being located in the lower layer, and the membrane treated in step (3) being immersed in the solution longitudinally at 30° C. for 1 hour;

[0079] (5) Dissolve NaBH4 in water, stir thoroughly to obtain a 0.2M NaBH4 solution, add KOH and adjust the pH to 11;

[0080] (6) Pour out the solutions on both sides, replace the upper solution with 0.2 M NaBH4 (pH = 11, KOH) obtained in step (5), and reduce at 30°C for 30 min;

[0081] (7) The membrane obtained in step (6) was taken out, washed three times with ultrapure water, treated with 5M HClO4 at room temperature for 48 h, treated with ultrapure water at 80°C for 30 min, and then washed with ultrapure water to obtain a composite membrane.

[0082] The Ir loading was 1 mg cm-1 sprayed on the Pt-impregnated side of the composite membrane. -2 The catalyst layer on the other side was sprayed with a Pt loading of 0.4 mg cm -2A catalyst layer is formed to obtain a catalyst coated membrane with hydrogen removal function.

[0083] Comparative Example 1

[0084] A Nafion 212 membrane was treated in 0.5 M H2SO4 at 80°C for 30 min, then in ultrapure water at 80°C for 30 min, and washed with water until the pH was 7 to obtain a treated membrane.

[0085] One side of the membrane was sprayed with Ir with a loading of 1 mg cm -2 The catalyst layer on the other side was sprayed with a Pt loading of 0.4 mg cm -2 The catalyst layer is formed to obtain a membrane electrode.

[0086] Comparative Example 2

[0087] (1) Dissolve Pt(NH3)4(NO3)2 in water, stir thoroughly to obtain a 0.4 mM Pt(NH3)4(NO3)2 solution, add KOH and adjust the pH to 13;

[0088] (2) Dissolve K2SO4 in water, stir thoroughly to obtain a 0.013M K2SO4 solution, add H2SO4, and adjust the pH to 1;

[0089] (3) treating the Nafion 212 membrane in 0.5 M H2SO4 at 80°C for 30 min, then treating it in ultrapure water at 80°C for 30 min, and washing it until the pH is 7 to obtain a treated membrane;

[0090] (4) According to Figure 2 The membrane is fixed in a manner such that the platinum-containing solution obtained in step (1) is located on the right, and the potassium sulfate solution obtained in step (2) is located on the left, and the membrane treated in step (3) is immersed in the solution at 30° C. for 24 hours;

[0091] (5) Dissolve NaBH4 in water, stir thoroughly to obtain a 0.2M NaBH4 solution, add KOH and adjust the pH to 11;

[0092] (6) Pour out the solutions on both sides, replace the upper solution with 0.2 M NaBH4 (pH = 11, KOH) obtained in step (5), and reduce at 30°C for 60 min;

[0093] (7) The membrane obtained in step (6) was taken out, washed three times with ultrapure water, treated with 5M HClO4 at room temperature for 48 h, treated with ultrapure water at 80°C for 30 min, and then washed with ultrapure water to obtain a composite membrane.

[0094] The Ir loading was 1 mg cm-1 by blade coating on the Pt-impregnated side of the composite membrane. -2The catalyst layer on the other side was coated with Pt with a loading of 0.4 mg cm -2 The catalyst layer is formed to obtain a membrane electrode.

[0095] Comparative Example 3

[0096] (1) Dissolve Pt(NH3)4(NO3)2 in water, stir thoroughly to obtain a 0.4 mM Pt(NH3)4(NO3)2 solution, add KOH and adjust the pH to 13;

[0097] (2) Dissolve K2SO4 in water, stir thoroughly to obtain a 0.013M K2SO4 solution, add H2SO4, and adjust the pH to 1;

[0098] (3) treating the Nafion 212 membrane in 0.5 M H2SO4 at 80°C for 30 min, then treating it in ultrapure water at 80°C for 30 min, and washing it until the pH is 7 to obtain a treated membrane;

[0099] (4) According to Figure 1 The membrane is fixed in a manner, with the platinum-containing solution obtained in step (1) being located in the upper layer, and the potassium sulfate solution obtained in step (2) being located in the lower layer, and the membrane treated in step (4) being immersed in the solution longitudinally at 30° C. for 1 hour;

[0100] (5) Dissolve NaBH4 in water, stir thoroughly to obtain a 0.2M NaBH4 solution, add KOH and adjust the pH to 11;

[0101] (6) The solutions on both sides were poured out, and the upper solution was replaced with 0.2 M NaBH4 (pH = 11, KOH) obtained in step (5), reduced at 30°C for 60 min, and washed three times with ultrapure water to obtain a composite membrane.

[0102] The Ir loading was 1 mg cm-1 sprayed on the Pt-impregnated side of the composite membrane. -2 The catalyst layer on the other side was sprayed with a Pt loading of 0.4 mg cm -2 The catalyst layer is formed to obtain a membrane electrode.

[0103] Comparative Example 4

[0104] (1) Dissolve Pt(NH3)4(NO3)2 in water, stir thoroughly to obtain a 0.4 mM Pt(NH3)4(NO3)2 solution, add KOH and adjust the pH to 13;

[0105] (2) Dissolve K2SO4 in water, stir thoroughly to obtain a 0.013M K2SO4 solution, add H2SO4, and adjust the pH to 1;

[0106] (3) treating the Nafion 212 membrane in 0.5 M H2SO4 at 80°C for 30 min, then treating it in ultrapure water at 80°C for 30 min, and washing it until the pH is 7 to obtain a treated membrane;

[0107] (4) According to Figure 1 The membrane is fixed in a manner, the potassium sulfate solution obtained in step (2) is located on the upper layer, the platinum-containing solution obtained in step (1) is located on the lower layer, and the membrane treated in step (3) is immersed in the solution longitudinally at 30° C. for 1 hour;

[0108] (5) Dissolve NaBH4 in water, stir thoroughly to obtain a 0.2M NaBH4 solution, add KOH and adjust the pH to 11;

[0109] (6) Pour out the solutions on both sides, replace the lower solution with 0.2 M NaBH4 (pH = 11, KOH) obtained in step (5), and reduce at 30°C for 60 min;

[0110] (7) The membrane obtained in step (6) was taken out, washed three times with ultrapure water, treated with 5M HClO4 at room temperature for 48 h, treated with ultrapure water at 80°C for 30 min, and then washed with ultrapure water to obtain a composite membrane.

[0111] The Ir loading was 1 mg cm-1 sprayed on the Pt-impregnated side of the composite membrane. -2 The catalyst layer on the other side was sprayed with a Pt loading of 0.4 mg cm -2 The catalyst layer is formed to obtain a membrane electrode.

[0112] Comparative Example 5

[0113] (1) Dissolve Pd(NH3)4(NO3)2 in water, stir thoroughly to obtain a 0.4 mM Pd(NH3)4(NO3)2 solution, add KOH and adjust the pH to 13;

[0114] (2) Dissolve K2SO4 in water, stir thoroughly to obtain a 0.013M K2SO4 solution, add H2SO4, and adjust the pH to 1;

[0115] (3) treating the Nafion 212 membrane in 0.5 M H2SO4 at 80°C for 30 min, then treating it in ultrapure water at 80°C for 30 min, and washing it until the pH is 7 to obtain a treated membrane;

[0116] (4) According to Figure 1 The membrane is fixed in a manner, the potassium sulfate solution obtained in step (2) is located at the lower layer, the palladium-containing solution obtained in step (1) is located at the upper layer, and the membrane treated in step (3) is immersed in the solution longitudinally at 30° C. for 1 hour;

[0117] (5) Dissolve NaBH4 in water, stir thoroughly to obtain a 0.2M NaBH4 solution, add KOH and adjust the pH to 13;

[0118] (6) Pour out the solutions on both sides, replace the upper solution with 0.2 M NaBH4 (pH = 11, KOH) obtained in step (5), and reduce at 30°C for 60 min;

[0119] (7) The membrane obtained in step (9) was taken out, washed three times with ultrapure water, treated with 1M H2SO4 at room temperature for 48 h, treated with ultrapure water at 80°C for 30 min, and then washed with ultrapure water to obtain a composite membrane.

[0120] The Pd-impregnated side of the composite membrane was sprayed with Ir at a loading of 1 mg cm -2 The catalyst layer on the other side was sprayed with a Pt loading of 0.4 mg cm -2 The catalyst layer is formed to obtain a membrane electrode.

[0121] like Figure 3 As shown, due to the effect of gravity, the Pt of the composite membrane in Comparative Example 2 is concentrated in the lower layer; due to the generation of bubbles, the Pt of the composite membrane in Comparative Example 4 is distributed in a point-like manner, and it is impossible to achieve uniform distribution in the entire membrane; Example 1 utilizes upper layer reduction to effectively discharge the gas generated by reduction, and at the same time utilizes longitudinal distribution to eliminate the influence of gravity in membrane impregnation, thereby achieving uniform distribution of precious metals in the composite membrane.

[0122] The loading of the hydrogen removal catalyst in the composite membrane of Examples 1-3 and Comparative Examples 1-5 was tested, and the full cell was assembled for water electrolysis test. The current density at 1.8 V and 500 mA cm -2 The hydrogen content in the anode oxygen at the current density is shown in Table 1.

[0123] Table 1 Test results of Examples 1-3 and Comparative Examples 1-5

[0124]

[0125] Depend on Figure 4 It can be seen that by comparing with Comparative Example 1, the composite membrane prepared by the impregnation method in Examples 1 and 2 utilizes the immersion of the dehydrogenation catalyst to in-situ oxidize the hydrogen diffused to the anode side, effectively reducing the hydrogen content in the oxygen on the anode side, which can well improve the safety of battery operation and avoid the risk of explosion. At the same time, combined with Table 1, it can be seen that the use of longitudinal impregnation of precious metals has no obvious effect on the battery performance of the full battery, while the membrane resistance of Comparative Example 3 is significantly increased due to the lack of acid washing, and the battery performance is significantly reduced. In Comparative Example 5, the addition of KOH affects the pH of the solution, and Pd is not well deposited. After acid washing, the remaining impregnation amount is almost 0, and the dehydrogenation function cannot be achieved.

[0126] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a composite proton exchange membrane, characterized in that: The method comprises the following steps: (1) dissolving a compound containing a noble metal ion in water, stirring thoroughly to dissolve, and adjusting the pH to 7 to 13 to obtain a solution S1; (2) dissolving K2SO4 in water, stirring thoroughly to dissolve, and adjusting the pH to 1 to 3 to obtain solution S2; (3) washing the proton exchange membrane M1 with acid and then with water to obtain an activated membrane M2; (4) adding solution S1 and solution S2 to both sides of the activated membrane M2 and immersing the membrane M3 in a longitudinal direction; the longitudinal direction means that the membrane is parallel to the bottom of the immersion container, and solution S1 and solution S2 are located on the upper and lower sides of the membrane, respectively; (5) dissolving NaBH4 in water, stirring thoroughly to dissolve, and adjusting the pH to 7 to 13 to obtain solution S3; (6) adding solution S3 to the upper side of membrane M3 for reduction treatment to obtain membrane M4; (7) The membrane M4 is acid-washed and water-washed to obtain the composite proton exchange membrane.

2. The method for preparing a composite proton exchange membrane according to claim 1, characterized in that: In the step (1), the molar concentration of the compound containing noble metal ions in the solution S1 is 0.4 to 4 mM; KOH is used to adjust the pH; In the step (2), the molar concentration of K2SO4 in the solution S2 is 0.01 to 0.1 M; H2SO4 is used to adjust the pH; In the step (3), the acid used for pickling is 0.5M H2SO4; In the step (5), the molar concentration of NaBH4 in the solution S3 is 0.2 to 1 M; KOH is used to adjust the pH; In the step (7), the acid used for pickling is HClO4 or H2SO4, and its molar concentration is 1 to 5M.

3. The method for preparing a composite proton exchange membrane according to claim 1, characterized in that: In the step (1), the compound containing precious metal ions is one or more of Pt(NH3)4(NO3)2, Pt(NH3)4Cl2, Pd(NH3)4(NO3)2, and Pd(NH3)4Cl2.

4. The method for preparing a composite proton exchange membrane according to claim 3, characterized in that: When the compound containing precious metal ions is a Pt compound, the pH in steps (1) and (5) is independently 10 to 13; when the compound containing precious metal ions is a Pd compound, the pH in steps (1) and (5) is independently 7 to 11; when the compound containing precious metal ions is a combination of a Pt compound and a Pd compound, the pH in steps (1) and (5) is independently 10 to 11.

5. The method for preparing a composite proton exchange membrane according to claim 1, characterized in that: In the step (3), the temperature of pickling and water washing is 80°C, the time of pickling is 30 to 60 minutes, and the time of water washing is 30 to 60 minutes; In the step (4), the immersion temperature is 30 to 40° C. and the immersion time is 1 to 24 hours; In the step (6), the reduction temperature is 30 to 40° C. and the reduction time is 30 to 90 min; In the step (7), the acid pickling temperature is 20°C, the acid pickling time is 12 to 48 hours, and the water washing temperature is 80°C, and the water washing time is 30 to 60 minutes.

6. A composite proton exchange membrane, characterized in that: Prepared by the method according to any one of claims 1 to 5.

7. A membrane electrode, comprising a composite proton exchange membrane, and an anode catalyst layer located on one side impregnated with a precious metal and a cathode catalyst layer located on the opposite side, characterized in that: The composite proton exchange membrane is the composite proton exchange membrane according to claim 6.

8. The membrane electrode according to claim 7, characterized in that: The anode catalyst layer comprises an anode catalyst and an ionomer 1, wherein the anode catalyst comprises one or more of an Ir-based catalyst, a Ru-based catalyst and an IrRu composite catalyst, and the ionomer 1 is a perfluorosulfonic acid resin; The cathode catalyst layer includes a cathode catalyst and an ionomer 2. The cathode catalyst includes one or more of a Pt-based catalyst and a Pd-based catalyst. The ionomer 2 is a perfluorosulfonic acid resin.

9. The membrane electrode according to claim 8, characterized in that: The anode catalyst includes Ir, IrOx, Ru, RuOx, IrRuOx, IrY alloy, RuY alloy, IrRuY alloy and corresponding catalysts with carriers, wherein Y is selected from one or more of Pt, Pd, Au, Ag, Fe, Co, Ni, Cu and Mn; The carrier includes one or more of carbon, titanium dioxide, and tungsten oxide.

10. The membrane electrode according to claim 8, characterized in that: The Pt-based catalyst includes one or more of Pt / C, Pt, and PtM alloys, and the Pd-based catalyst includes one or more of Pd / C, Pd, and PdM alloys, wherein M is selected from one or more of Ir, Ru, Au, Co, Fe, Cu, and Ni.

Citation Information

Patent Citations

  • Proton exchange membrane water-electrolyzer with internal hydrogen removing function and producing method thereof

    CN104726891A

  • Catalyst coating proton membrane with composite catalyst layer structure, preparation method of catalyst coating proton membrane and water electrolysis equipment

    CN116926618A

  • Preparation of proton exchange membrane electrode for electrolyzing water

    CN101463487A

  • New method for depositing Pt nano particles on surface of Nafion proton exchange membrane

    CN102903944A

  • Preparation method and system of proton exchange membrane

    CN113594521A